Pandangan Terhadap Ahl Al-Kitab: Kontroversi Tanpa AKhir: Views on the People of the Book: An Endless Controversy - Zainal Anshari; Zainuddin Zainuddin (Fenomena, 2017)
The concept of Ahl al-Kitab (People of the Book) in Islam has long generated ongoing debate, particularly regarding its inclusive yet distinctive recognition of non-Muslim religious communities. This study aims to examine the terminological and interpretive development of Ahl al-Kitab in the Qur’an, hadith, and classical and contemporary Islamic scholarship, as well as its practical implications for social interaction, especially concerning food and marriage. Using a library research method with a descriptive-analytical approach, this study analyzes primary sources including Qur’anic exegesis, hadith collections, and works of fiqh and tafsir. The findings reveal that while the majority of scholars limit Ahl al-Kitab to Jews and Christians, a significant minority—including Abu Hanifah, Muhammad Abduh, and Muhammad Rasyid Ridlo—argue for a broader inclusion of Zoroastrians, Sabians, Hindus, Buddhists, and Confucians on the basis that every nation has received a divine messenger. Furthermore, divergent legal opinions persist regarding the permissibility of consuming meat slaughtered by Ahl al-Kitab and intermarriage with them. The study concludes that the flexible interpretation of Ahl al-Kitab offers a theological basis for cosmopolitanism and interfaith coexistence, but recommends contextual fatwas aligned with contemporary realities. Konsep Ahl al-Kitab dalam Islam telah melahirkan kontroversi berkepanjangan terkait pengakuan terhadap komunitas non-Muslim tanpa menyamakan semua agama. Penelitian ini bertujuan mengkaji perkembangan terminologis dan penafsiran Ahl al-Kitab dalam al-Qur’an, hadis, serta pemikiran ulama klasik dan kontemporer, beserta implikasinya terhadap interaksi sosial seperti makanan dan pernikahan. Menggunakan metode penelitian kepustakaan dengan pendekatan deskriptif-analitis, penelitian ini menganalisis sumber-sumber primer seperti tafsir, kitab hadis, dan fiqih. Hasil penelitian menunjukkan bahwa meskipun mayoritas ulama membatasi Ahl al-Kitab pada Yahudi dan Nasrani, sebagian signifikan lain—termasuk Abu Hanifah, Muhammad Abduh, dan Muhammad Rasyid Ridlo—memperluas cakupan tersebut meliputi Majusi, Shabi’un, Hindu, Buddha, dan Konghucu dengan argumentasi bahwa setiap umat memiliki rasul. Selain itu, perbedaan pendapat masih kuat mengenai kehalalan sembelihan Ahl al-Kitab dan pernikahan dengan mereka. Kesimpulannya, penafsiran fleksibel tentang Ahl al-Kitab memberikan landasan teologis bagi kosmopolitanisme dan koeksistensi antaragama, namun merekomendasikan fatwa kontekstual yang sesuai dengan realitas zaman modern.